Perbandingan Analisis Rasio Laporan Keuangan Perusahaan Sektor Pertambangan Tahun 2019 – 2023 - Alif, Fajar Ardian Nur; Magitasiwi, Zufi Yustika; Ridho, M Wachid; Wahyu, Windiana; Cahyani, Wandira Regita Putri; Hidayati, Cholis (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study was conducted to analyze the comparison of financial ratio reports for companies in the mining sector during the 2019-2023 period. The research employed a descriptive quantitative method using secondary data obtained from the Indonesia Stock Exchange. The results showed that, based on the liquidity ratio, PT Bukit Asam Tbk demonstrated good financial conditions, while PT Aneka Tambang Tbk required further observation. Based on the activity ratio, PT United Tractors and PT Aneka Tambang required further observation, whereas PT Tembaga Mulia Semanan Tbk showed good financial conditions. Based on the solvency ratio, PT Bukit Asam Tbk and PT United Tractors Tbk exhibited more stable and profitable performance. This stability was also reflected in their profitability ratios, which showed consistent performance, and the same applies to their market ratios.